Characterisation of stress corrodes specimen - Azmie, Mohd Ariffin (Universiti Malaysia Perlis (UniMAP), 2012)
Characterisation of stress corrodes specimen is to investigate on the surface of failure specimens after stress corrosion specimen test and reveal the morphology for immersed and unimmersed specimen using Scanning Electron Microscopic (SEM). The stress corrosion test were carried out on heat treated Aluminium 6063(Al 6063) that been immersed in 3.5 wt % Sodium Chloride (NaCl) solution at room temperature. The unaged heat treatment was carried out at 520ºC for 2 hours while the artificial ageing heat treatment was carried out at 200ºC ageing temperature for 4, 6 and 8 hours respectively. Specimens will be immersed for 1200 hours in NaCl solution. Tensile stress will be carried out to all the specimens. A fractography study via scanning electron microscopy performed on the surface of failure stress corrodes specimen will revealed the different morphology between the specimens.